The GOAL‐Hēm journey: Shared decision making and patient‐centred outcomes. Issue 5 (21st June 2022) - Roberts, Jonathan C.; Richardson, Sharon; Miles, Moses E.; Stanley, Justin; Chapman, Chere A. T.; Denne, Michael; Caicedo, Jorge; Rockwood, Kenneth; Recht, Michael
Abstract: Introduction: GOAL‐Hēm is a novel, haemophilia‐specific, patient‐centred outcome measure (PCOM) based on goal attainment scaling, allowing people with haemophilia (PwH) to set and monitor the attainment of individualized goals for treatment. Aim: To provide a thorough overview of the creation, validation, and development of GOAL‐Hēm. Methods: Clinician workshops were held to develop a haemophilia‐specific goal menu. Qualitative data from semistructured interviews with PwH and their caregivers guided further revisions to the goal menu (i.e., goal domains and descriptors). A feasibility study was performed including a 12‐week, prospective, noninterventional evaluation involving clinicians and PwH at four US haemophilia treatment centres. Finally, the Patient Voice Study gathered feedback from PwH and their caregivers via an online survey, interviews, and a focus group. Results: The feasibility study validated GOAL‐Hēm with successful outcomes in construct/content validity and responsiveness, including a large effect in patient‐ and clinician‐rated goal attainments. The Patient Voice Study led to significant refinement of GOAL‐Hēm goals and descriptors, resulting in a more straightforward and relatable menu for PwH and their caregivers. Overall, GOAL‐Hēm captured qualitative data in areas important to PwH and employed quantitative methods to evaluate meaningful changes in those areas. The individualized tool was well equipped to handle the complex and chronic nature of haemophilia and was endorsed by PwH, their caregivers, and clinicians. Conclusion: The GOAL‐Hēm development journey may serve as a roadmap for other PCOMs in a variety of settings, including clinical studies, haemophilia treatment centres for care planning, and as a tool to gather real‐world evidence.